Optimization of Maintenance Systems Based on Oil Analysis - Glos, Josef; Sejkorová, Marie; Nguyen, Trung Tin (Kaunas University of Technology, 2016)
The aim of this article is to estimate system soft failure occurrence and residual technical life in order to optimise firmly planned preventive maintenance. To do this, selected data oil analysis from oil field data are analysed. The importance of the proper use oil analysis is not always entirely clear for all users. It may be a strategy that says when oil must be replaced, or is used in order to determine when and where a failure occurs in the vehicle. It can be understood as a way of reducing the severity of disorders groups of vehicles or their frequency. Most often, oil analysis program combines the continuous attention of oil or disruptions groups of vehicles.
Optimalizace údržby systémů na základě analýzy oleje
Keywords: tribotechnical diagnostics; oil; FTIR spektrometry; atomic emission spektrometry; maintenance; tribotechnická diagnostika; FTIR spektrometrie; atomová emisní spektrometrie; spolehlivost